Standard specification for Heat-Treated Carbon Steel Joint Bars, Microalloyed Joint Bars, and Forged Carbon Steel Compromise Joint Bars (American Society for Testing and Materials, 2006)
This specifification covers heat-treated carbon steel joint bars, microalloyed joint bars, and forged compromise joint bars for general use in standard railroad track.